Initial Experiences of Laparoscopic Surgery at Nobel Medical College Teaching Hospital: A Learning Curve - Subedi, Shanti; GC, Narayan; Lamichhane, Sabina; Chhetri, Manisha (Journal of Lumbini Medical College, 2017)
Introduction: The field of minimal invasive surgery has flowered explosively in the recent past. Modern endoscopy has  changed  the  approach  to  diagnosis  as  well  as  the  operative  procedure. This  study  was  done  with  the  aim  of sharing  the  experiences  of  gynecological  laparoscopic  procedures  done  at  Nobel  Medical  College  and  Teaching Hospital, Nepal.Methods: A descriptive study was done in the department of Obstetrics and Gynecology, Nobel Medical College from 1stFebruary 2015 to 30thJanuary 2016. All the patients undergoing laparoscopic procedures were analyzed for the indication, type of procedures and their complications.Results: During the study period, 100 patients underwent laparoscopic procedures including 25 cases of diagnostic and 75 cases of therapeutic procedures. Fifty-three patients with an ovarian mass underwent laparoscopic cystectomy. Laparoscopic salpingectomy was done in 11 patients with ectopic pregnancy. Laparoscopy assisted vaginal hysterectomy (LAVH) was done in eight cases and laparoscopic sterilization in two cases. One patient underwent successful myomectomy. One patient undergoing laparoscopic cystectomy and one case of LAVH had conversion to laparotomy because of dense adhesion and vault bleeding respectively. No other major complication noted apart from port side bleeding, infection and vault hematoma.Conclusion:  Laparoscopy  is  a  safe  and  feasible  alternative  to  open  gynecological  surgeries  though  it  has  a  long learning curve and a lot of expertise is necessary.DOI: https://doi.org/10.22502/jlmc.v4i1.77J. Lumbini. Med. Coll.Vol 4, No 1, Jan-June 2016, page: 20-23